Radiogenomics: the search for genetic predictors of radiotherapy response. (December 2014) - Kerns, Sarah L; L West, Catharine M; Andreassen, C Nicolaj; Barnett, Gillian C; Bentzen, Søren M; Burnet, Neil G; Dekker, Andre; Ruysscher, Dirk De; Dunning, Alison; Parliament, Matthew; Talbot, Chris; Vega, Ana; et al.
ABSTRACT : 'Radiogenomics' is the study of genetic variation associated with response to radiotherapy. Radiogenomics aims to uncover the genes and biologic pathways responsible for radiotherapy toxicity that could be targeted with radioprotective agents and; identify genetic markers that can be used in risk prediction models in the clinic. The long-term goal of the field is to develop single nucleotide polymorphism-based risk models that can be used to stratify patients to more precisely tailored radiotherapy protocols. The field has evolved over the last two decades in parallel with advances in genomics, moving from narrowly focused candidate gene studies to large, collaborative genome-wide association studies. Several confirmed genetic variants have been identified and the field is making progress toward clinical translation.